Finance and Development, June 1993. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1993)
SlNCE the dissolution of the Soviet Union, most of the former member states have retained the ruble as their national currency but have followed independent monetary policies. Such a combination is not sustainable. With mounting disarray in the ruble area, each state must now quickly adopt either a common monetary policy or a separate national currency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet